2020
DOI: 10.12659/msm.919270
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of 1-Level Corpectomy and 2-Level Discectomy for Cervical Spondylotic Myelopathy: A Finite Element Analysis

Abstract: Background: Anterior cervical discectomy and fusion (ACDF) and anterior cervical corpectomy and fusion (ACCF) are effective treatments for cervical spondylotic myelopathy (CSM), but it is unclear which is better. In this study, we compared the biomechanical properties of 2-level ACDF and 1-level ACCF. Material/Methods: An intact C3-C7 cervical spine model was developed and validated, then ACDF and ACCF simulation models were developed. We imposed 1.0 Nm moments and displacement-controlled loading on the C3 sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…For all FE models, we constrained the C7 lower endplate in all six directions and set a reference point on the C3 upper endplate. An axial preload of 73.6 N was applied to simulate physiological compression [ 25 ]. A 1-Nm moment load was then employed to produce flexion, extension, lateral bending, and axial rotation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For all FE models, we constrained the C7 lower endplate in all six directions and set a reference point on the C3 upper endplate. An axial preload of 73.6 N was applied to simulate physiological compression [ 25 ]. A 1-Nm moment load was then employed to produce flexion, extension, lateral bending, and axial rotation.…”
Section: Methodsmentioning
confidence: 99%
“…The validity of the current FE model was demonstrated by comparing the intervertebral ranges of motion (ROM) of the intact model with those of previous studies [ 26 29 ]. To reduce the influence of ROMs and other index changes, caused by different prostheses, the overall ROMs of the experimental model and control model had to be consistent [ 15 , 19 , 25 ]. Hence, a displacement-control loading that equaled that of the intact model was applied to the ACCF and MACDVC-AM model to compare the intervertebral ROMs.…”
Section: Methodsmentioning
confidence: 99%
“…Various loading conditions are applied to perform the FE analysis in the previous research. Ouyang et al (2020) applied a physiological compression of about 7.5 kg and 1,000 Nm moment on the superior endplate of the C3 vertebra in the intact model, then applied the movement angle acquired in the intact model to the ACDF model (Ouyang et al, 2020). The 1,000 Nm moment in their research kept the same magnitude as the load applied in the Panjabi et al (2001), allowing the comparison of ROMs between the in silico model and in vitro model.…”
Section: Modeling Methodsmentioning
confidence: 99%
“…Researchers reported an in-silico analysis of the cervical-related surgery and concluded various treatment suggestions based on the reduced Von Mises stress of joint facets or endplates, restricted ROMs, etc. (Ng and Teo, 2001;Li et al, 2017;Ouyang et al, 2019Ouyang et al, , 2020Zhou et al, 2022), while limited investigations demonstrated the effective insilico method to predict the surgical outcomes of deformity correction. Moreover, in most existing in-silico studies, the modeling method and the computational consideration have not been stated clearly, which may leave confusion for replication.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it can be concluded that a precise model of degenerated facet joints is essential for predicting future changes in facet joint loads following disc degeneration. FEM models have also been performed for the biomechanical investigation of various methods for managing multilevel myelopathy of the cervical spine [47][48][49][50][51]. For instance, in a recent study, an intact C2-C7 spine model was generated.…”
Section: Degenerative Disc Diseasementioning
confidence: 99%